Spatio-Temporal Transformation in Agricultural Land-Use Pattern in Karachi Using Geo-Spatial Techniques: A Case Study along West Bank of Malir River - Anila Kausar,; Khalida Mahmood,; Razzaq Ahmed, (Journal of Basic & Applied Sciences, 2014)
The study attempts to investigate spatio-temporal transformation along the west bank of Malir River in Karachi between 2005 and 2013, using geo-spatial techniques. The major objective of this study is to find out the changes occurring in the pattern of land use along Malir River in various administrative units of Karachi division. The study indicates changes in agricultural land during the period covered by the study. These changes which are all related to agricultural land are mainly explained by transformation occurring in terms of various land-use. Due to the unavailability of statistical data at grass root level, primary data have been collected from imageries to obtain different land-use categories. The results show that considerable changes have been witnessed in the entire study area. This kind of research is very useful for all agricultural areas around major cities of the Asia and Africa in terms of land-use change detection.